THE INFLUENCE OF CAPITAL ADEQUACY, NON-PERFORMING FINANCING, LIQUIDITY, AND OPERATIONAL EFFICIENCY ON PROFITABILITY OF ISLAMIC BANKS - Muhammad Roihan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The measure of profitability in the banking industry that is used in general is Return on Equity (ROE) and Return on Assets (ROA). In this case, the profit proxy used is Return on Assets (ROA) because ROA focuses on the company's ability to earn profits in its operations, while ROE only measures the return from the investment sector of the company owner in the business. In this study, we will see how the effect of capital adequacy will be proxied by the Capital Adequacy Ratio (CAR), Problem Financing which will be proxied by the Non Performing Financing (NPF), Liquidity which will be proxied by the Financing to Deposit Ratio (FDR) and Operational Efficiency which will be proxied by the ratio of Operational Expenses to Operational Income (BOPO). The results of the study show that there is a influence of variable independent (CAR, NPF, FDR, BOPO) simultaneously on variables dependent it (ROA). Partially only the CAR variable which shows a significant positive positive effect and BOPO which shows a significant negative effect on profitability (ROA). While the other two variables, namely NPF and FDR, have no significant effect on profitability (ROA).